MODELLING MORAL VALUES AND NATURE IN PANTUN HERITAGE: MALAY THOUGHT ON MANNERS AND KNOWLEDGE AMONG CHILDREN - Hairulliza Mohamad Judi; Nik Suhaila Yasmina Nik Khalili; Ifwat Amzar Amirham (Journal of Islamic, Social, Economics and Development, 2023)
Pantun forms a longstanding Malay literature composition which depicts the finesse of values and nature. Pantun highlights thoughts, emotions, experiences, hopes and sentiments of the society. The delicate words softly promoting noble values and identity among society members, be they a father, a teacher or a child. Being the most valuable assets to a nation, children requires proper preparation to address ever-changing trend and new technology while maintaining their spirit to be functional to the society. To revive pantun in the society, so as to sustain the opportunity for children to appreciate nature and listen to advices, this research intend to design and develop mobile game for this purpose, in the long run. However, proper understanding of related background is required to assist children to explore moral values and nature in pantun. Therefore, this study aims to propose a model of exploring morality and nature in pantun among children using game. The research applies an extensive review of previous research. The suggested model reveals the application of Social Constructivist Theory and Malay Poetic Theory. By focusing on pedagogical approaches together with literature and culture, respectively, both provides the expected benefits and sustainability of pantun to the younger generation. Providing better understanding of nature and moral values to children means preparing the future generation with as many morality and noble values of humanity, as well as to live in success and harmony.